EVALUASI KEBERHASILAN PROGRAM INSEMINASI BUATAN PADA TERNAK SAPI BALI DI KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Angel Matuakotta; Demianus Ferdinand Souhoka; Jeffrie Wattimena (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aimed to evaluate the success of the artificial insemination (AI) program in Bali cattle in Amahai Subdistrict, Central Maluku Regency. Key reproductive performance indicators analyzed included the number of acceptors, conception rate (CR), service per conception (S/C), and non-return rate (NRR). The results revealed that the highest CR was observed in Makariki Village (91.5%) and the lowest in Soahuku Village (66.7%). A very strong negative correlation was found between CR and S/C (r = -0.94), while a very strong positive correlation was observed between CR and NRR (r = 0.999). These findings highlight the critical role of reproductive management and the need to enhance inseminator competence to improve the effectiveness of AI programs in Bali cattle.